Factors affecting digital transformation of enterprises in Binh Duong province - Bui, Thị Hường (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
The 4th Industrial Revolution (Industry 4.0) has opened up many opportunities for businesses to access technology to optimize costs and increase business profits. Therefore, the article has studied the factors affecting the digital transformation of enterprises in Binh Duong province. The results show that there are 7 factors affecting the digital transformation of enterprises in Binh Duong province, which are: Legal policy and government support; Safety and confidentiality of enterprise information; Digitization process; Digital transformation strategy of enterprises; Logistics services and customer support; Human resources of the enterprise; Organizational structure and business processes of the enterprise.